THEORETICAL-METHODOLOGICAL ASPECTS OF BACKGROUNDS TO EDUCATIONAL ACTIVITY FORMATION OF PRESCHOOL AGED CHILDREN - Nadejda V. Babinova; Ludmila V. Voronina (Образование и наука)
The purpose of the paper is selection and justification background components to teaching activity and indicators of its formedness among preschool children.Results. The alternatives of using project activity for forming backgrounds for learning activities of high preschool aged children are shown as a form of learning process organization. The concepts «learning activity» and «general learning activities» are considered. The conditions of project activity realization in preschool education organizations are determined.Scientific novelty. The concept «backgrounds for learning activities» is defined; it is proposed to consider it as necessary certain qualities for the emergence of personal, regulatory, cognitive and communicative aspects of learning activities that reflect different aspects of training activity.Practical significance. The research implementations can be used in the teacher’s practice at pre-school education, and in the family education.